Elementary. Language Practice with key. English Grammar and Vocabulary - Vince M. Michael (Oxford, Macmillan, 2010)
Elementary Language Practice is the reference and practice book for students at elementary / A2 level. Now in full colour, this new edition retains all the original features which make the Language Practice series so popular, including clear grammar explanations, plenty of practice and regular review units. Themed vocabulary units contextualize essential elementary level words and phrases, offering a variety of exercise types to help students understand and use the new vocabulary. The accompanying CD-ROM includes extra practice for all the units covered in the book, with exercises based on international computer-based test types. The test generator includes 1,000 items to test students on all areas covered by the book.